RANCANG BANGUN PERANGKAT RUMAH CERDAS PENCEGAHAN KEBAKARAN BERBASIS IOT - Hadriansa Hadriansa; Puji Nurahmiyati; Hafizhan Zulhilmi (Journal of Innovation And Future Technology (IFTECH), 2024)
Various technologies, including the Internet of Things (IoT), aim to streamline system functionalities. IoT finds application in diverse sectors, notably Smart Homes, enhancing household tasks and bolstering security via internet-connected devices. This study investigates IoT's utilization in detecting different types of smoke—combustion smoke from various sources like cigarettes, paper, and gas. The trials involved testing the MQ2 sensor's efficacy in detecting smoke at varying distances. In testing this device the author conducted several trials on several types of combustion smoke, cigarette smoke, paper combustion smoke and gas. In these trials, the authors obtained several tests of distance differences in detecting smoke using the MQ2 sensor. The devices made in this study have been adjusted to the purpose of the study. The important conclusion of this study is the need to understand the specifications of the device at the beginning of the study, so as not to use 2 (two) microcontrollers